Generalized Scalar Duffin-Kemmer-Petiau Electrodynamics (GSDKP) - Bufalo, R. [UNESP]; Cardoso, T. R. [UNESP]; Nogueira, A. A. [UNESP]; Pimentel, B. M. [UNESP]; IOP (Iop Publishing Ltd, 2016)
The main goal of this work is to investigate the quantum interaction between scalar field and gauge field in the context of Generalized Scalar Duffin-Kemmer-Petiau Electrodynamics (GSDKP) by a quantum theory in the functional approach. The Hamiltonian structure is obtained with the Dirac method and the Faddeev-Senjanovic procedure is established in order to write the transition amplitude in an alternative gauge fixing, known as the non-mixing gauge. As a consequence, the Schwinger-Dyson-Fradkin equations and the Ward-Takahashi-Fradkin identities are obtained.